Concretos refratários avançados contendo nano-óxidos produzidos pelo Método Pechini - Alves Júnior, José Antonio (2018)
Recently there is a great effort to use the benefits of nanometric powders additions in the matrices of advanced refractory concretes of ; low (LC), ultra low (ULC) and no cement (NC) refractory concretes, in order to make their microstructures more resistant to corrosion and thermal shock damage. The common routes consist in the addition of nano-oxides of refractory phases of interest in the form of colloidal liquid or pre prepared powder. These during the firing of the concretes result in particles that are not really nanometric, but rather sub-micrometric or even micrometrics, which decreases their potential benefits. In this work, aiming the in situ development of nano oxide particles of Al, Mg and Cr, for better thermo mechanical properties, polymer resins produced by the Pechini Method, were added to advanced concretes (LC, ULC and NC) typical compositions, serving doubly as a kneading liquid for the refractory concretes and at the same time as a source of nano-oxides to the refractory concretes matrices. There is an important difference between this type of in situ development of nanoparticles and those derived from pre-prepared nanometric particles, considering that in the liquid resins the metals are in atomic condition, so that during the pyrolysis and oxidation of the same, the oxides will originate in nascent state, that is, in a truly nano scale, besides being highly reactive and more homogeneously distributed throughout the matrix. The results demonstrated that the inclusion of the liquid resins promoted a significant improvement in the thermomechanical properties of all the concretes when compared to those of no resin addition. Also for comparative grounds, it was prepared individually from each resin, its respective nano oxide powder. These were added to the mass of the refractory concretes in the same proportion of those obtained upon pyrolysis and oxidation of the resins. The results did not show any improvement in the thermomechanical properties comparatively to the in situ development of nano oxides by addition of the liquid resins.